Pengaruh Pengelolaan Diri Siswa dan Karakter Guru Terhadap Prestasi Belajar Siswa Kelas X SMK Satya Widya Surabaya dan SMK Tri Tunggal Surabaya - Abdul Malik; Suryaman; Retno Danu Rusmawati (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
Education is basically a conscious effort to develop the potential of students by facilitating their learning activities. A nation is said to be advanced when the quality of its human resources is good, while the quality of human resources itself depends on the quality of its education. Given the importance of the role of education in people's lives, the government seeks to improve the quality of education, including improving the quality of students' abilities.The purpose of this study was to determine the effect of Self Regulated Learning (student self-management) and teacher character on student learning achievement. The type of research used in this study is correlational with a quantitative approach, where this study intends to determine the relationship of a variable to other variables. Data collection is obtained by conducting tests, questionnaires and documents. Data analysis using the Two Way Anova test. The results of the study show that: (1) There is the effect of Self Regulated Learning on student learning achievement, (2) There is a guidance for Teacher Character on student achievement, (3) Interaction between Self Regulated Learning and Teacher Character on student achievement.